2005
DOI: 10.1177/0734371x04272360
|View full text |Cite
|
Sign up to set email alerts
|

Public Employees With High Levels of Public Service Motivation

Abstract: More than a decade ago, Perry and Wise popularized the concept of public service motivation. Yet today, still little is known about public employees with high levels of public service motivation. This study sought to fill this gap in the literature by investigating the relationship that exists between public service motivation and the personal characteristics, management level, and monetary preferences of public employees. The findings reveal that public service motivation is significantly related to the gende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
65
1
9

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(85 citation statements)
references
References 32 publications
6
65
1
9
Order By: Relevance
“…Research indicates that public sector employees have a different motivation profile in terms of values, inclination to public service activities and volunteering (Bright (2005), Rotolo and Wilson (2006)). Researchers in the area of public administration have explored the idea that public service motivation is central to the effective delivery of public goods and services (Perry and Wise 1990).…”
Section: Public Service Motivationmentioning
confidence: 99%
“…Research indicates that public sector employees have a different motivation profile in terms of values, inclination to public service activities and volunteering (Bright (2005), Rotolo and Wilson (2006)). Researchers in the area of public administration have explored the idea that public service motivation is central to the effective delivery of public goods and services (Perry and Wise 1990).…”
Section: Public Service Motivationmentioning
confidence: 99%
“…Bright (2005), kamu hizmeti motivasyonunu çeşitli değişkenler bakımından sınadığı çalışmada, kadınlarda, yöneticilerde ve eğitim düzeyi yüksek olanlarda kamu hizmeti motivasyonunun daha yüksek olduğunu ortaya koymuştur. Öztürk ve Dündar (2003), kamu çalışanlarını motive eden faktörleri konu edindikleri çalışmada üç Bakanlığın (Adalet Bakanlığı, Sağlık Bakanlığı ve Milli Eğitim Bakanlığı) merkez örgütünde görev yapan farklı pozisyondaki yönetici ve çalışanların görüşlerini araştırmıştır.…”
Section: Kamu Hizmeti Motivasyonuunclassified
“…We have not tested whether specific interventions (for example, variations in leadership, autonomy, or tasks) can increase prosocial attitudes, and a number of crosssectional studies have suggested that we find higher levels of PSM when employees have been led transformationally, when they hold leadership positions or have experienced HR management tools, such as job enrichment or professional development Bright 2005;Giauque, Anderfuhren-Biget, and Varone 2013). Another panel study reported that PSM increases when people get older, and it decreases with every year that an employee works for the same public organization (Vogel 2012).…”
Section: Limitationsmentioning
confidence: 99%